A mechanistic investigation of corrosion-driven organic coating failure on magnesium and its alloys - Geraint Williams (npj Materials Degradation, 2019)
The failure mechanism of model organic coatings from Mg alloy surfaces is characterised by a combination in-situ scanning Kelvin probe analysis and time lapse photography. Initiation of underfilm corrosion by application of group I chloride salts to a penetrative coating defect produces an apparent cathodic-driven coating delamination, where the disbondment distance increases linearly with time at high relative humidity, although filiform corrosion (FFC) is also observed in the vicinity of the defect. The disbondment process occurs both in the presence and absence of oxygen, indicating that hydrogen evolution comprises the predominant underfilm cathodic reaction. Post-corrosion elemental analysis of the delaminated region shows an abundance of group I cation, but no chloride. When magnesium chloride or HCl are used to initiate corrosion, then only FFC is produced. The mechanism is discussed in terms of net anodic dissolution at the defect coupled with underfilm cathodic hydrogen evolution, producing organic coating disbondment under conditions where cations are able to transport ionic current within a zone of increased pH.